Traumatic experiences resulting from the war trauma 2014 and its relationship to psychological alienation among students of secondary schools in the Gaza Strips - EL-Naami, Sami; Zammouchi , Redhouane (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
The study aimed to identify the level of high school students' exposure to the traumatic experiences resulting from the 2014 war and the level of psychological alienation in their schools in the Gaza Strip. In addition, the current study explores the relationship between traumatic experiences, psychological alienation and some demographic variables. The researcher used the descriptive analytical approach. The study population consisted of (98214) male and female students, and the sample was (386) high school students from the secondary schools of Gaza Strip. The sample was chosen randomly from northern Gaza, the middle area and southern Gaza. Three grades were included; (grade 10,11 and 12) To achieve the study aims, two tools were used; the traumatic experiences scale, and the psychological alienation scale for adolescents. The study results revealed that the level of exposure of high school students in Gaza Strip schools regarding the traumatic experiences resulting from the 2014 war was (66.39%). Additionally, the level of psychological alienation reached (77.4%). Also, the findings showed that there was statistically significant centrifugal positive relationship between traumatic experiences on the one hand and psychological alienation and its dimensions on the other hand. In the same regard, the results revealed that there were no differences attributed to the gender variable in the scale of traumatic experiences. On the contrary, there were differences attributed to the gender variable in the psychological alienation scale in favor of males.